Literasi Konsumsi Rokok pada Remaja Berdasarkan Peraturan Pemerintah Nomor 28 Tahun 2024 (Studi di Kota Langsa) - Radhali, Radhali; Aldino, Hanri; Iqbal, Muhammad; Ulya, Zaki (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
Cigarette consumption among teenagers has become a trend in itself, causing them to forget about health. This problem in the regulations for controlling addictive substances in tobacco products as contained in Government Regulation (PP) Number 28 of 2024 concerning Implementing Regulations of Law Number 17 of 2023 concerning Health is in the public spotlight. In particular, regulations regarding retail cigarette sales, restrictions on cigarette advertising, and health warnings on cigarette packaging have been regulated in accordance with the norms of Article 434 paragraph (1). In this PKM activity, carrying out cigarette consumption literacy among teenagers in Langsa City aims to increase teenagers' knowledge about the dangers of consuming cigarettes and regulations regarding the prohibition of consuming cigarettes for teenagers in Langsa City, as well as encouraging teenagers to protect their health from the dangers of consuming cigarettes. In this way, teenagers in Langsa City are expected to be aware of the importance of maintaining health and regulating cigarette consumption for teenagers in Langsa City.